Livestock and Fish enabling innovation for value chain transformation flagship review and plans - Okike, Iheanacho (International Livestock Research Institute, 2015)
Acho Okike to the CGIAR Research Program on Livestock and Fish review and planning meeting, 23-26 March 2015